Viridis: Lux castellum - Da Silva Leote, Rosangela [UNESP] (Association for Computing Machinery (ACM), 2019)
The main goal of the conference is to promote the interest in the current digital culture and its intersection with art and technology as an important research field, and also to create a common space for discussion and exchange of new experiences. It seeks to foster greater understanding about digital arts and culture across a wide spectrum of cultural, disciplinary, and professional practices. To this end, many scholars, teachers, researchers, artists, comput-er professionals, and others who are working within the broadly defined areas of digital arts, culture and education across the world, submitted their innovative work to the conference.
Keywords: 3D Printing; Art; Art installation; Interactive object; Media Art